Microwave-Photonics Frequency Up-Converter for Telecom and Measurement Equipment. (April 2019) - Fofanov, D A; Bakhvalova, T N; Alyoshin, A V; Belkin, M E; Sigov, A S
Abstract: An ultra-wideband tunable frequency converter scheme for microwave and millimeter-wave signal generation based on optical recirculating loop and microwave-photonics technique, is proposed and demonstrated. The scheme consists of standard, commercially available elements such as dual parallel Mach-Zehnder modulator, optical filter, wideband photodiode and does not require ultra-broadband RF components. A recirculating loop acts as an optical frequency comb generator and allows obtaining multiple local oscillator signals at frequencies that significantly higher than the RF reference used. Up-converted signals of frequencies in mm-wave band are demonstrated experimentally with spectra free of spurious products. The converter proposed could be used as an alternative solution to microwave mixers in telecom and measurement equipment.